The role, importance and role of ecotourism in the development of the state in foreign countries - Khakimova Kamola Rakhimjonovna; Bekzod Abduhalilov Komiljonovich (Zien Journals, 2023)
this article cites information on the role, importance and role of ecotourism in the development of the state in foreign countries, models of use of national parks in the development of ecotourism and recreational tourism, American model, European model, park reservation model, Asian model and Australian models
Keywords: ecotourism; model; recreation; tourism